Impact of sewage sludge on the soil bacterial communities by DNA microarray analysis - Val-Moraes, Silvana P. [UNESP]; Marcondes, Jackson [UNESP]; Carareto Alves, Lucia M. [UNESP]; Lemos, Eliana G. M. [UNESP] (Springer, 2011)
Sewage sludge has been used as organic manure to replace chemical fertilizer. The aim of this study was to evaluate the effect of doses of sewage sludge on the soil bacterial community by DNA microarray analysis. A microarray phylochip containing 1,560 partial sequences of 16S rRNA from the most common strains of bacteria was developed for bioprospection. Soil plots from an experimental field in Brazil were assessed with or without sludge treatment containing different doses of nitrogen based on that recommended for maize cultivation. The microarray technique was useful for quickly assessing changes in the bacterial communities and a high variation was observed, mainly in soil treated with high doses of sludge. While sludge containing 25 kg N/ha favored an in crease in the number of members in various phyla, on the other hand sludge with the higher dose regarding to 200 kg N/ha caused a reduction in the number of members in almost all phyla. Proteobacteria often dominant in soils was specifically affected. This study highlights the spread of bacteria to new environments and provides direct information about bacterial composition at specific habitats. Our results have shown that bacterial community structure was greatly affected by sludge application.
Keywords: Bacterial community structure; 16S rRNA; Organic manure; Nitrogen impact